2008
DOI: 10.1016/j.jcrs.2007.10.030
|View full text |Cite
|
Sign up to set email alerts
|

Corneal endothelial decompensation after iris-claw phakic intraocular lens implantation

Abstract: A 25-year-old man received iris-claw phakic intraocular lenses (pIOLs) (Artisan, Ophtec) of -11.5 diopters (D) in the right eye and -13.0 D in the left eye; both pIOLs had a 6.0 mm optic and 8.5 mm haptics. Twenty months postoperatively, the best corrected visual acuity was 20/400 in the right eye and 20/25 in the left eye. Slitlamp examination revealed microcystic bullae, keratic precipitates, stromal edema, and ciliary injection in both eyes. Central corneal thickness was 704 microm in the right eye and 639 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 6 publications
0
14
0
1
Order By: Relevance
“…However, corneal decompensation after Artisan IOL implantation has been reported and may have been caused by excessive eye rubbing because of itching or by an anterior shift of the IOL due to its loose fixation to the iris surface. 25,26 Therefore, exact, firm fixation of the IOL in an area with sufficient iris tissue is essential to protect the corneal endothelium. Koss and Kohnen 27 found that the postoperative ACD was shallower in smaller eyes than in longer eyes and suggest performing posterior enclavation of iris-fixated IOLs in smaller eyes to ensure a safe distance between the IOL and the corneal endothelium.…”
Section: Discussionmentioning
confidence: 99%
“…However, corneal decompensation after Artisan IOL implantation has been reported and may have been caused by excessive eye rubbing because of itching or by an anterior shift of the IOL due to its loose fixation to the iris surface. 25,26 Therefore, exact, firm fixation of the IOL in an area with sufficient iris tissue is essential to protect the corneal endothelium. Koss and Kohnen 27 found that the postoperative ACD was shallower in smaller eyes than in longer eyes and suggest performing posterior enclavation of iris-fixated IOLs in smaller eyes to ensure a safe distance between the IOL and the corneal endothelium.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al 21 recently reported a case of corneal decompensation in a patient with Artisan pIOLs in which incorrect enclavation of the pIOL resulted in movement of the IOL toward the posterior corneal surface. In our case, there were no signs of increased mobility of the pIOL with eye movements, which could explain the localized decrease in ECD.…”
Section: Discussionmentioning
confidence: 99%
“…However, when implanted anterior to the iris, the risks of endothelial cell loss and bullous keratopathy remain. 8 This risk decreases slightly in retropupillary implantation.…”
mentioning
confidence: 99%